When VP Ellipsis is Bled: Locative Inversion and Specificational Copulars - Sunjoo Choi; Myung-Kwan Park (영어학, 2021)
The licensing element for VP ellipsis has for long been a controversial issue. Tense (Zagona 1988), Spec-head agreement on T (Lobeck 1994), and sentential polarity focus (López 1995) have been put on the table on the issue on a VP ellipsis-licensing element. In this paper we argue by examining locative inversion (LI) and specificational copular (SC) constructions vis-à-vis their kin that sentential polarity focus is a proper licensing element for VP ellipsis. Characteristically, LIs and SCs bear (presentational) focus feature on a markedly postposed subject DP inside a VP (relative to topic feature on a markedly preposed locative phrase in clause-initial position), which in turn precludes the occurrence of sentential polarity focus outside the VP. The ban on both VP ellipsis and VP anaphora in LIs and SCs is thus accounted for by the absence of such focus in need. By contrast, apparently similar and related constructions such as pseudo-LIs & existenials with ‘there’ in [Spec,TP] and equative copulars that encode sentential polarity focus are fine with VP ellipsis and VP anaphora. KCI Citation Count: 0